KANONIČKE RELACIJE PROCJENA VJEŽBANJA U SLOBODNOM VREMENU I PARAMETARA OPĆEG STATUSA ODRASLIH MUŠKARACA - Mirna Andrijašević; Žarko Bilić; Dobromir Bonacin (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In this research, we process 319 male entities aged 19-57 years from Middle Bosnia. Initial data were collected with questionnaire that concerns 16 variable, 9 for free time estimation and 7 for estimation of global status. Data were processed with canonical correlation analysis. Inside total sample we found bimodal character of value system connected with exercise. First canonical factor shows an existence of real value of exercise in free time, mostly with middle aged entities with families and job oriented people without enough free time. Second canonical factor identify younger people, without business or family obligations, but without systematic tendencies of exercise in free time regime, and with excuses for avoiding such activities. It was concluded that serious educational actions should be applied for this situation change with entities of both types of explained behavior. Family people should fi nd better offer of organized activities, and for other (probably younger) it is necessary to apply more basic education about total quality of actual status and future life.